Socialization of the Early Savings Movement in Sukaslamet Village, Kroya District, Indramayu Regency - Fatkhudin; Didik Himmawan (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2025)
Socialization is one of the means that influences a person's personality. Socialization is usually referred to as a theory of roles (role theory). Because in the process of socialization, the roles that must be played by individuals are taught. Saving is currently an important thing. Saving has been instilled early on by some parents to their children. Because savings have an important role in the future. Saving means setting aside some of the money we have to be saved. Saving is one way to manage money. The easiest way to save is at home because it can be done at any time. Having a habit of saving is clearly very useful for our future. Saving is saving a certain amount of money so that it can be used later if needed. The more money saved, the better. This activity is one of the devotion of knowledge that I can do in the series of KKN processes. Carrying out activities that can be beneficial for children in Sukaslamet Village, this activity is the main goal in every program